1989
DOI: 10.1039/p19890002111
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of cordifolin A, a novel cucurbitacin from Fevillea cordifolia, using one and two dimensional n.m.r. techniques

Abstract: Cordifolin A (3) [3~,16~~-dihydroxy-20,25-epoxy-l9(10 -9P)-abeo-1 O~-lanost-5-en-I 1,22dione] was isolated from the methanol-soluble fraction of the 1% tartaric acid extract of dried seeds of Fevillea cordifolia L. (Cucurbitaceae) used in Jamaican folk medicine. Structure elucidation was based primarily on the use of multi-pulse n.m.r. techniques, especially combination of long range and direct 'H,'H INADEQUATE and 'H, 13C chemical shift correlation spectra. Biosynthesis of this novel triterpene apparently inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…125 Kinoin C (190) is a member of the 22,23,24,25,26,27hexanorcucurbitacin group, which was also found in some other plants. In addition to the siraitic acids (126)(127)(128)(129)(130) isolated from Siraitia grosvenori, other cucurbitane acids, such as rosacea acids A (191) and B (192) from kuhonggu (Russula rosacea), 126 and lepida acid A (193) from R. lepida, 127 have been reported. From Fevillea cordifolia, cordifolin A (194) and its glycoside (195), and cordifolins B (196) and C (197) were obtained.…”
Section: -(Or 29-) Norcucurbitacins Plants Of the Genusmentioning
confidence: 99%
See 1 more Smart Citation
“…125 Kinoin C (190) is a member of the 22,23,24,25,26,27hexanorcucurbitacin group, which was also found in some other plants. In addition to the siraitic acids (126)(127)(128)(129)(130) isolated from Siraitia grosvenori, other cucurbitane acids, such as rosacea acids A (191) and B (192) from kuhonggu (Russula rosacea), 126 and lepida acid A (193) from R. lepida, 127 have been reported. From Fevillea cordifolia, cordifolin A (194) and its glycoside (195), and cordifolins B (196) and C (197) were obtained.…”
Section: -(Or 29-) Norcucurbitacins Plants Of the Genusmentioning
confidence: 99%
“…,124 Kinoins A (188), B (189),C (190) and their corresponding glycosides have been obtained from Ibervillea sonorae (Cucurbitaceae) 125. In addition to the siraitic acids(126)(127)(128)(129)(130) isolated from Siraitia grosvenori, other cucurbitane acids, such as rosacea acids A (191) and B (192) from kuhonggu (Russula rosacea),126 and lepida acid A (193) from R. lepida,127 have been reported. In addition to the siraitic acids(126)(127)(128)(129)(130) isolated from Siraitia grosvenori, other cucurbitane acids, such as rosacea acids A (191) and B (192) from kuhonggu (Russula rosacea),126 and lepida acid A (193) from R. lepida,127 have been reported.…”
mentioning
confidence: 99%
“…These data suggested the presence of a highly oxygenated C 30 cucurbitacin. Comparison of the 1 H NMR and 13 C NMR data with those of 6 (cordifolin A, from Fevillea cordifolia) [6] revealed that the structure of compound 1 is very similar to that Table 1. NMR data of 1 a and 6, and key HMBC correlations and ROEs of 1.…”
Section: Resultsmentioning
confidence: 81%
“…Scheme 3 nuclear correlation spectra (COLOC 29 and HETCOR 30,31), and one dimensional nuclear Overhauser effect (NOE) difference ~p e c t r o s c o p y , ~~. ~~for the structural elucidation of 2 is analogous to that reported for cordifolin A 1 21. When 1 is used as a reference compound in the spectral analysis of compound 2, close similarities are observed between the two molecules in rings B, C, D and E. Ring A provided the major point of difference.…”
mentioning
confidence: 82%
“…20 Recent examination of the seeds of Fevillea cordifolia L. (Cucurbitaceae) led to the isolation and structure elucidation of a novel pentacyclic triterpene, cordifolin A 1. 21 Application of multi-pulse NMR methods proved to be essential to obtain the structure of 1 which displays extensive resonance overlap. Further investigation of the plant extract allowed us to purify three more cucurbitacins 2-4.…”
mentioning
confidence: 99%